How terrorist groups end: lessons for countering Al Qa'ida - Jones, Seth G. (Rand Corporation monograph series, 2008)
How terrorist groups end -- Policing and Japan's Aum Shinrikyo -- Politics and the FMLN in El Salvador -- Military force and Al Qa'ida in Iraq -- The limits of America's Al Qa'ida strategy -- Ending the 'war' on terrorism